Verifying Biblical Allusions in John 1:51: A Methodological Framework for Genesis Reception Studies - Tułodziecki, Tomasz (The Biblical Annals, 2026)
Current methodologies for identifying biblical allusions in the Fourth Gospel, while extensive, often struggle with texts that operate through imagery and metaphor. This study applies a tripartite framework – textual flow analysis, image analysis, and intertextual verification – to demonstrate that John 1:51 constitutes a deliberate allusion to Jacob’s dream (Gen 28:12). The methodology reveals that the allusion operates through recontextualization: the Son of Man replaces both Jacob’s ladder and the divine figure, creating a new christological revelation theology. While multiple intertextual connections may be present (including Dan 7), the Genesis reception proves central to the text’s mystagogical function. The applied verification shows semantic, structural, and functional correspondences between the texts, confirming systematic Genesis reception in the Johannine narrative. This synchronic approach, though it yields specific insights into the text’s faith-formational purpose, represents one methodological option among others. The framework contributes to ongoing discussions about allusion verification in biblical texts, particularly for passages where imagery carries the primary allusive weight. The results demonstrate that authentic allusions function not through simple borrowing, but through deliberate theological recontextualization that preserves original narrative function while establishing new meaning paradigms.